REPLENISHMENT COST OF A STORAGE SYSTEM MODELLED THROUGH A DEFECTIVE RENEWAL EQUATION - Ferreira, Manuel Alberto (Acta Scientiae et Intellectus, 2024)
A storage system where a k units stock is replaced instantaneously, when required, is presented in this work. It is also supposed a Poisson demand. It is proved that the storage system replenishment cost expected present value function fulfills a defective renewal equation, being proposed for it an asymptotic expression.